A Analysis of Ecoenzyme Characteristics from Combination of Fruit Peel Waste - Triyatdipa, Haqil; Agustien, Anthoni; Marlina, Marlina (Biospecies, 2025)
Indonesia encounters many significant challenges in organic waste management, with 37.87% of the total 38.7 million tonnes of national waste (in 2024) unmanaged. Organic waste, such as fruit peels, which are often dumped into landfill, contributes to greenhouse gas emissions and environmental pollution. Ecoenzyme, a fermentation product of organic waste (1:3:10 ratio of sugar, substrate, water), is emerging as an innovative solution for waste conversion into value-added products. Besides reducing waste volume, ecoenzymes produce ozone (O₃) that suppresses the greenhouse effect, antimicrobial acetic acid, and natural cleaning compounds. Fruit peels such as orange, banana, papaya, watermelon and pineapple are potential substrates due to their cellulose and pectin content, but the characteristics of ecoenzyme depend on the interaction of chemical (pH, Total Acid Titration/TTA) and biological (Lactic Acid Bacteria/BAL, yeast) parameters. Previous studies focused on ecoenzymes based on one type of fruit peel, while the potential of combinations of various fruit peels has not been explored holistically. This study aims to analyse the characteristics of fruit peel combination ecoenzymes through evaluation of chemical (pH, TTA) and microbiological (LAB population, yeast) parameters. The results are expected to provide scientific guidance for the production of high-quality ecoenzymes while supporting sustainable organic waste reduction strategies.